Emerging water insecurity in India: lessons from an agriculturally advanced state - AERA (Agricultural Economics Research Review, 2023)
The growing scarcity of water is one of the biggest challenges for economic development in world, especially in the developing countries because of its excess demand over limited or fixed supply. Agriculture is the largest consumer of water but its household demand apart from that in other economic sectors such as industry and energy has been growing rapidly because of growing population and changing lifestyles (urbanization). Not only that, the water use efficiency in agriculture is low. In future, developing economies are likely to face severe water crisis, and India is no exception.